Low interfacial resistivity in CoSi2/ZrCoSb thermoelectric junctions. (April 2022) - Xiong, Bowen; Fu, Chenguang; Han, Shen; Li, Airan; Zhao, Xinbing; Zhu, Tiejun
Abstract: Both p-type and n-type M CoSb ( M = Ti, Zr, Hf) half-Heusler compounds have been found to exhibit high thermoelectric performance for power generation, but there is still a lack of research on the suitable interfacial materials to connect both p-type and n-type M CoSb for device assembly. Here, CoSi2 was selected as the electrode to connect p-type Hf0.5 Zr0.5 CoSb0.8 Sn0.2 and n-type (Hf0.6 Zr0.4 )0.88 Nb0.12 CoSb, and the interfacial microstructure and interfacial contact resistivity were studied before and after thermal aging. In both types of thermoelectric junctions, the interface layer with a thickness from several to tens of μm is formed, which ensures a good bonding strength. The interfacial contact resistivity of both as-sintered thermoelectric junctions was less than 1 μΩ cm 2, which rises to 3–4 μΩ cm 2 after aging for 8 days at 1, 073 K and keeps almost unchanged during the longer aging treatment. The present work demonstrates that CoSi2 is a suitable electrode material for both p- and n-type M CoSb due to the good bonding strength and the low interfacial resistivity, which paves the way for the applications of M CoSb-based TE materials. Graphical abstract: Image 1 Highlights: CoSi2 was selected as the electrode to connect both p-type and n-type M CoSb-based TE compounds. Both types of TE junctions exhibit the low interfacial resistivity after long-term thermal-aging. CoSi2 can be used as potential electrode material for the applications of M CoSb-based TE materials.